Tooth modification and dynamic performance of the cycloidal drive. (15th February 2017) - Ren, Zhong-Yi; Mao, Shi-Min; Guo, Wen-Chao; Guo, Zheng
Abstract: A new method of cycloid disc tooth modification is presented in this paper. Its main idea is to design the modification clearance curves to adapt to different modification targets. A detailed procedure of the new modification clearance curve, which can be defined by adjusting the position of 5 key points is developed. Numerical experiments are carried out to verify the effectiveness of the new method. A Multi-DOF nonlinear dynamic model of cycloidal speed reducer is established, then the cycloid disc rotational displacement and rotational velocity versus time of different modification clearance are solved by the Runge-kutta numerical method. The results show that this method can improve the carrying capability of cycloidal drive, eliminate noise and vibration and develop the transmission accuracy. Highlights: A new method of cycloid disc tooth modification is presented in this paper. New method is to design the modification clearance curves actively. We can define the position of minimum clearance. We can define the modification values on the heel and toe end of gear teeth. New method can improve the carrying capability and dynamic performance.